Dickkopf-3 is upregulated in osteoarthritis and has a chondroprotective role. Issue 5 (May 2016) - Snelling, S.J.B.; Davidson, R.K.; Swingler, T.E.; Le, L.T.T.; Barter, M.J.; Culley, K.L.; Price, A.; Carr, A.J.; Clark, I.M.
Summary: Objective: Dickkopf-3 (Dkk3) is a non-canonical member of the Dkk family of Wnt antagonists and its upregulation has been reported in microarray analysis of cartilage from mouse models of osteoarthritis (OA). In this study we assessed Dkk3 expression in human OA cartilage to ascertain its potential role in chondrocyte signaling and cartilage maintenance. Methods: Dkk3 expression was analysed in human adult OA cartilage and synovial tissues and during chondrogenesis of ATDC5 and human mesenchymal stem cells. The role of Dkk3 in cartilage maintenance was analysed by incubation of bovine and human cartilage explants with interleukin-1β (IL1β) and oncostatin-M (OSM). Dkk3 gene expression was measured in cartilage following murine hip avulsion. Whether Dkk3 influenced Wnt, TGFβ and activin cell signaling was assessed in primary human chondrocytes and SW1353 chondrosarcoma cells using qRT-PCR and luminescence assays. Results: Increased gene and protein levels of Dkk3 were detected in human OA cartilage, synovial tissue and synovial fluid. DKK3 gene expression was decreased during chondrogenesis of both ATDC5 cells and humans MSCs. Dkk3 inhibited IL1β and OSM-mediated proteoglycan loss from human and bovine cartilage explants and collagen loss from bovine cartilage explants. Cartilage DKK3 expression was decreased following hip avulsion injury. TGFβ signaling was enhanced by Dkk3 whilst Wnt3a and activin signaling were inhibited. Conclusions: We provide evidence that Dkk3 is upregulated in OA and may have a protective effect on cartilage integrity by preventing proteoglycan loss and helping to restore OA-relevant signaling pathway activity. Targeting Dkk3 may be a novel approach in the treatment of OA.